INDICATORS OF MILITARY CAPABILITIES OF ENEMY SABOTAGE-RECONNAISSANCE GROUPS AND THEIR MODELLING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the process of modelling combat operations and to organize the fight against sabotage-intelligence groups, estimates of their combat capability indicators have been derived and suggested.